Effects of frozen storage time on bovine serum and plasma concentrations of macrominerals and indicators of energy balance - A. Valldecabres; E.M. Sitko; L. Horan; Á. García-Muñoz; S.T. Butler (Journal of Dairy Science)
ABSTRACT: Concentrations of macrominerals and markers of energy balance are often determined in samples that have been stored frozen for a period of time. The objective of this study was to compare concentrations of Ca, P, Mg, nonesterified fatty acids (NEFA), and BHB determined in serum and plasma samples after separation of whole blood within 24 h of collection (fresh sample) and after storage at −18°C for 3 or 6 mo. Nonhemolyzed blood samples collected into lithium heparin or nonadditive tubes from 76 dairy cows at 21 ± 9 d postpartum (mean ± SD) were used in this study. Serum or plasma was harvested into separate aliquots within 6 h of sample collection for testing as fresh (stored at 4°C until testing within 24 h of sample collection; baseline) or after 3 or 6 mo of storage at −18°C on a wet chemistry analyzer. We observed effects of sample type (serum vs. plasma) on P, Mg, and NEFA concentrations and effects of storage time (0 vs. 3 or 6 mo) on Ca, P, Mg, NEFA, and BHB concentrations. In addition, effects of storage time were conditional to the sample type for P and BHB concentrations. Effects of sample type and storage for up to 3 mo were minimal, potentially biologically and diagnostically irrelevant for all the evaluated analytes. However, storage for 6 mo may have relevant effects on Ca, P, and BHB concentrations. Compared with baseline, the Ca concentration after 6 mo of storage was 0.27 mmol/L less (95% CI = −0.31 to −0.22 mmol/L). Phosphorus and BHB concentrations were significantly less after 6 mo of storage, but the difference varied according to sample type (in mmol/L; P: −0.11 [95% CI = −0.30 to −0.25] in serum and −0.06 [95% CI = −0.26 to −0.21] in plasma; BHB: −0.27 [95% CI = −0.36 to −0.18] in serum and −0.18 [95% CI = −0.23 to −0.13] in plasma). In conclusion, the effects of sample type and storage for up to 3 mo at −18°C were minimal, but the potential effects of longer durations of frozen storage on concentrations of Ca, P, and BHB should be considered. Further research is needed to corroborate findings from this study and to describe optimum storage conditions for samples when timely testing is not feasible.